Histones link inflammation and thrombosis through the induction of Weibel–Palade body exocytosis. (November 2016) - Michels, A.; Albánez, S.; Mewburn, J.; Nesbitt, K.; Gould, T. J.; Liaw, P. C.; James, P. D.; Swystun, L. L.; Lillicrap, D.
Abstract : Essentials Dysregulated DNA and histone release can promote pathological immunothrombosis. Weibel‐Palade bodies (WPBs) are sentinel‐like organelles that respond to proinflammatory stimuli. Histones induce WPB exocytosis in a caspase, calcium and charge‐dependent mechanism. A targetable axis may exist between DNA/histones and WPBs in inflammation and immunothrombosis. Summary: Background: Damage‐associated molecular patterns (DAMPs), including molecules such as DNA and histones, are released into the blood following cell death. DAMPs promote a procoagulant phenotype through enhancement of thrombin generation and platelet activation, thereby contributing to immunothrombosis. Weibel–Palade bodies (WPBs) are dynamic endothelial cell organelles that contain procoagulant and proinflammatory mediators, such as von Willebrand factor (VWF), and are released in response to cell stresses. VWF mediates platelet adhesion and aggregation, and has been implicated as a procoagulant component of the innate immune response. Objective: To determine the influence of histones and DNA on WPB release, and characterize their association in models of inflammation. Methods: We treated C57BL/6J mice and cultured endothelial cells with histones (unfractionated, lysine‐rich or arginine‐rich) and DNA, and measured WPB exocytosis. We used inhibitors to determine a mechanism of histone‐induced WPB release in vitro . We characterized the release of DAMPs and WPBs in response to acute and chronic inflammation in human and murine models. Results and conclusions: Histones, but not DNA, induced the release of VWF (1.46‐fold) from WBPs and caused thrombocytopenia (0.74‐fold), which impaired arterial thrombus formation in mice. Histones induced WPB release from endothelial cells in a caspase‐dependent, calcium‐dependent and charge‐dependent manner, and promoted platelet capture in a flow chamber model of VWF–platelet string formation. The levels of DAMPs and WPB‐released proteins were elevated during inflammation, and were positively correlated in chronic inflammation. These studies showed that DAMPs can regulate the function and level of VWF by inducing its release from endothelial WPBs. This DAMP–WPB axis may propagate immunothrombosis associated with inflammation.